Imperatives in English and Acehnese - Putri Nurhayati (English Education Journal, 2018)
The objective of this study is to explain the differences between imperatives in English and Acehnese and also to scrutinize the types and functions of imperatives in English and Acehnese. To achieve the objective of this study, the writer designed a qualitative study. The subject of this study was the people of Acehnese and the books of English and Acehnese, and the object of this study was imperative sentences. The writer collected some theories and opinions of experts from different resources to support the research. To collect the data, the writer used the following instruments: documentation and interview. The data were analyzed by applying a contrastive analysis to compare and find out the differences and similarities of imperatives in English and Acehnese. Based on the result, it was found that the types of imperatives in English and Acehnese are comparatively the same, i.e. positive imperative and negative imperatives. There are seven functions of imperative in English. They are as command, request, suggestion, prohibition, advice, invitation and direction. Meanwhile in Acehnese, there are nine functions of imperative. They are as command, prohibition, request, suggestion, invitation, advice, direction, compulsion and let imperative. Acehnese imperative sentence always use prefix of personal pronoun neu, ta, ka. From this fact, it can be concluded that there are slight differences of imperatives between English and Acehnese.